Sistematización de la experiencia práctica de intervención de la evaluación de clima laboral en la empresa EP Petroecuador, en el año 2017. - Orrego Galárraga, Shannon Melisa (2018)
The systematization of the work climate assessment was carried out, from the experience experienced during the execution of the project in EP PETROECUADOR company at a national level in 2017; given that there was a need to implement improvements in this area and the important thing was to obtain statistical data that allowed us to observe from different perspectives how it work climate. Considering that the evaluation was carried out at the national level, the data obtained were generated, by area, by question and by a comparison between them. At the beginning, the instruments that served to make an initial collection of information for the project were the participant observation, the documentary analysis and the interview, after obtaining these data, for the systematization, the survey was used as a method of data collection. applied in the five zones in which the company is located, which are north-central, north-western, south, southwest and east; taking a sample of the population formed by three hundred and fifty four respondents divided into different zones, which were chosen at random.